Ultrahigh-efficiency desalination via a thermally-localized multistage solar still. Issue 3 (7th February 2020) - Xu, Zhenyuan; Zhang, Lenan; Zhao, Lin; Li, Bangjun; Bhatia, Bikram; Wang, Chenxi; Wilke, Kyle L.; Song, Youngsup; Labban, Omar; Lienhard, John H.; Wang, Ruzhu; Wang, Evelyn N.
Abstract : Passive vapor generation systems combining interfacial solar heating and vaporization enthalpy recycling enable high-efficient low-cost desalination. Abstract : Passive vapor generation systems with interfacial solar heat localization enable high-efficiency low-cost desalination. In particular, recent progress combining interfacial solar heating and vaporization enthalpy recycling through a capillary-fed multistage architecture, known as the thermally-localized multistage solar still (TMSS), significantly improves the performance of passive solar desalination. Yet, state-of-the-art experimental demonstrations of solar-to-vapor conversion efficiency are still limited since the dominant factors and the general design principle for TMSS were not well-understood. In this work, we show optimizing the overall heat and mass transport in a multistage configuration plays a key role for further improving the performance. This understanding also increases the flexibility of material choices for the TMSS design. Using a low-cost and free-of-salt accumulation TMSS architecture, we experimentally demonstrated a record-high solar-to-vapor conversion efficiency of 385% with a production rate of 5.78 L m −2 h −1 under one-sun illumination, where more than 75% of the total production was collected through condensation. This work not only significantly improves the performance of existing passive solar desalination technologies for portable and affordable drinking water, but also provides a comprehensive physical understanding and optimization principle for TMSS systems.